Design and development of lion dance robot - Anu, Sadanandan Geethamany (2013)
Robotic hobby kits are widely using in electronic market nowadays. It is getting popularity day by day. This is a study, design and implementation of a lion dance movements in a robot as a hobby kit. After the completion, robot has to perform lion dance. Currently used kit is Bioloid and there are limitations and constraints using this kit. This report includes a detailed study of Bioloid premium robot kit and how this project can be improved in order to achieve a smooth transition movement of the robot.